Evaluation of the microbiota present in toothbrushes of infant patients during hospitalization: Pilot study (Research, Society and Development, 2021)
This study aimed to evaluate the possible nosocomial bacterial contamination of toothbrushes from pediatric patients and correlate these findings with the storage conditions. The study was developed with patients admitted to a public hospital in Rio de Janeiro. Only patients hospitalized for at least three days in the pediatric ward were included. Oncologic, immunosuppressed, and patients with severe respiratory infections were excluded. Ten personal toothbrushes were collected and immediately transferred to the Microbiology Laboratory. Bacterial identification was carried out by selective culture media, Gram stain, and biochemical tests (urea hydrolysis, indole, catalase, and conjugated coagulase). Furthermore, antimicrobial sensitivity tests were performed to detect methicillin-resistant and vancomycin-resistant Staphylococcus aureus. Patient's age and hospitalization period were 10.5 years and 8.8 days in mean. Thirty-three toothbrushes were stored exposed to the hospital environment, without any protection. Acinetobacter spp. were identified in 33% and Pseudomonas aeruginosa in 22% of the samples. Additionally, a total of 11% of samples were contaminated by methicillin-resistant and vancomycin-resistant Staphylococcus aureus. Nosocomial bacterial contamination of toothbrushes, including by antibiotic-resistant Staphylococcus aureus, was frequent and strongly associated with their direct exposure to the hospital environment. These results emphasize the importance of implementing strategies to prevent the bacteria contamination of hospitalized patient’s toothbrushes.